Kajian Psikologi Positif Konsep Ikigai pada Kaisar Akihito dalam Akihito Tennou Monogatari - Aqiilah Bilqiis Salsabiil Harahap; Yusida Lusiana; Heri Widodo (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2021)
The aim of this study is to explain the relationship between the concept of Ikigai and eudaimonic happiness also with the psychological well-being of Emperor Akihito. This research is a descriptive qualitative type. The data were collected using literature study techniques which are sourced from Akihito Tennou Monogatari manga. The results found that the concept of Ikigai in Emperor Akihito, both in the form of characteristics and Ikigai pillars, all reflected Aristotle's eudaimonic happiness because it was in accordance with the virtue of an emperor, which is being a good emperor with the ability to embrace all his people and establish positive relationships with the international world. The concept of Ikigai also reflects six aspects of Ryff's psychological well-being, that is consist of 1) self-acceptance, 2) positive relationships with others, 3) autonomy, 4) environmental mastery. ), 5) purpose in life, and 6) personal growth. The conclusion is that Emperor Akihito was able to achieve eudaimonic happiness as well as psychological well-being by being a good emperor as a form of his Ikigai.